2017
DOI: 10.3892/mmr.2017.7487
|View full text |Cite
|
Sign up to set email alerts
|

Targeting strategies of adenovirus-mediated gene therapy and virotherapy for prostate cancer

Abstract: Prostate cancer (PCa) poses a high risk to older men and it is the second most common type of male malignant tumor in western developed countries. Additionally, there is a lack of effective therapies for PCa at advanced stages. Novel treatment strategies such as adenovirus-mediated gene therapy and virotherapy involve the expression of a specific therapeutic gene to induce death in cancer cells, however, wild-type adenoviruses are also able to infect normal human cells, which leads to undesirable toxicity. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…Gene therapy has brought about a breakthrough for the treatment of prostate cancer, and a number of studies have identified a substantial number of genes that may be potential targets for the treatment of this malignancy (11,12). In the present study, AIPC cell lines PC3 and DU145, which do not respond to androgens, glucocorticoids or epidermal/fibroblast growth factors, were selected as models (13,14). In addition, the cisplatin-resistant subline of PC3, PC3/DDP, was used.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy has brought about a breakthrough for the treatment of prostate cancer, and a number of studies have identified a substantial number of genes that may be potential targets for the treatment of this malignancy (11,12). In the present study, AIPC cell lines PC3 and DU145, which do not respond to androgens, glucocorticoids or epidermal/fibroblast growth factors, were selected as models (13,14). In addition, the cisplatin-resistant subline of PC3, PC3/DDP, was used.…”
Section: Introductionmentioning
confidence: 99%
“…Development of effective PCa gene therapies was the objective of many research groups and numerous publications detail their findings (e.g. [56][57][58][59][60][61]. Some gene therapies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are five early transcription units (E1A, E1B, E2, E3 and E4), two delayed transcription units (IX and Iva2) and one late transcription unit (L1-L5) in Ad 5 coding region [7]. E1A conserved region 2 (E1A-CR2) interacts with retinoblastoma (Rb) in host cells to promote S-phase entry and viral DNA replication [7]. E1B contains E1B-19K and E1B-55K.…”
Section: Genome Structure Of Admentioning
confidence: 99%